2017
DOI: 10.12659/msmbr.904563
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study: The Significance of Combined Testing of Serum Markers for Diagnosis of Rheumatoid Arthritis

Abstract: BackgroundThere have been few studies on the value of various antibody combinations in rheumatoid arthritis (RA) diagnosis, and a lack of studies with large sample sizes, especially in the Chinese population. This study retrospectively evaluated the diagnostic value of a combined assay of five auto-antibodies [anti-cyclic citrullinated peptide (anti-CCP), anti-keratin (AKA), anti-RA 33, glucose-6-phosphate isomerase (GPI), and rheumatoid factor (RF)] for RA.Material/MethodsData were obtained from 5,725 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To demonstrate excellent accuracy, the value of AUC should be more than 0.97, and AUC of 0.75-0.92 is considered to be good [43]. AUC value was 0.7194 in this study implied that AKA had a moderate diagnostic accuracy, and it was higher than in previous study [25].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…To demonstrate excellent accuracy, the value of AUC should be more than 0.97, and AUC of 0.75-0.92 is considered to be good [43]. AUC value was 0.7194 in this study implied that AKA had a moderate diagnostic accuracy, and it was higher than in previous study [25].…”
Section: Discussionmentioning
confidence: 48%
“…They finally named it anti-keratin antibody (AKA) [22]. In previous studies, it was found that a specificity of AKA was from 79 to 100% in the diagnosis of RA [23,24], whereas its sensitivity ranged from 20 to 80% [25,26]. Therefore, in order to determine whether AKA can be used as an auxiliary diagnostic serum marker for RA, we carried out this meta-analysis.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…After excluding this study, the AUC, sensitivity, and specificity were 0.84, 0.86, and 0.73, respectively. In the series analysis, influence evaluation ( Figure 8D ) and outlier detection ( Figure 8D ) found three studies 43 45 that might influence the robustness of the conclusions. After omitting the three studies, the AUC, sensitivity, and specificity were 0.90, 0.64, and 0.96, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the strict inclusion and exclusion criteria, 24 published papers were included in this meta-analysis, 2245 including 21 combined in series and 8 combined in parallel. In total, 7151 cases of RA and 5913 controls were included.…”
Section: Resultsmentioning
confidence: 99%